A ten-year study of immunogenicity and safety of the AS04-HPV-16/18 vaccine in adolescent girls aged 10-14 years. Issue 7 (3rd August 2019) - Schwarz, Tino F.; Huang, Li-Min; Valencia, Alejandra; Panzer, Falko; Chiu, Cheng-Hsun; Decreux, Annabelle; Poncelet, Sylviane; Karkada, Naveen; Folschweiller, Nicolas; Lin, Lan; Dubin, Gary; Struyf, Frank
ABSTRACT: This study assessed long-term immunogenicity and safety following 3 doses of AS04-adjuvanted human papillomavirus (HPV)-16/18 L1 virus-like particle (VLP) vaccine in females 10–14 years old. Girls included in the immunogenicity subset in the primary controlled, observer-blinded, randomized study (NCT00196924) who received 3 doses were invited for a 10-year follow-up (NCT00316706 and NCT00877877). Serum antibody responses against HPV-16/18 (vaccine types) and HPV-31/45 (non-vaccine types) were measured by enzyme-linked immunosorbent assay (ELISA) using type-specific VLP as coating antigens. Serious adverse events (SAEs) and pregnancy information were recorded. At Month (M) 120, all subjects (N = 418, according-to-protocol immunogenicity cohort) were seropositive for anti-HPV-16/18 antibodies. Geometric mean titers (GMTs) were 1589.9 ELISA Units [EU]/mL (95% confidence interval [CI]: 1459.8–1731.6) for anti-HPV-16 and 597.2 EU/mL (95% CI: 541.7–658.5) for anti-HPV-18 in subjects seronegative at baseline for the type analyzed. Post hoc mathematical modeling predicted a durability ≥50 years for anti-HPV-16 and anti-HPV-18. For the non-vaccine humoral type response, all initially seronegative subjects had seroconverted at M7, with anti-HPV-31 GMT of 2030.5 EU/mL (95% CI: 1766.2–2334.4) and anti-HPV-45 GMT of 2300.8 EU/mL (95% CI: 2036.8–2599.0). At M120, 87.7% and 85.1% remained seropositive for anti-HPV-31 with GMT of 242.9 EU/mL (95% CI: 201.4–293.0) and anti-HPV-45 with GMT of 204.7 EU/mL (95% CI: 170.0–246.6). During the 10-year follow-up, no SAEs or abnormal pregnancy outcomes were causally related to vaccination. Three doses of the AS04-HPV-16/18 vaccine induced high and sustained antibody response against HPV-16, 18, 31 and 45 in girls aged 10–14 years during the 10-year follow-up, with an acceptable long-term safety profile.